Microplastic Abundance and Characteristics in The Soil Around the Jambi Talang Gulo Landfill - Lestari, Kiki Dewi (UIN Sulthan Thaha Saifuddin Jambi, Pusat Kajian Lingungan Hidup, 2024)
Microplastics are micro-sized plastic particles formed when plastic debris degrades due to direct sunlight, weather, and environmental factors. Talang Gulo Landfill is a trash disposal facility in Jambi. The Talang Gulo landfill's high trash volume raises the danger of pollution in the surrounding area. The goal of this study is to determine the number of microplastics, the types of microplastic polymers, and the distribution of microplastics in the Talang Gulo Jambi dump. The sampling approach was utilized in the study, with three random sample locations chosen to reflect locations surrounding the landfill. The study's findings revealed that the third sample included the greatest microplastics in soil samples near the Talang Gulo Jambi dump, at 1.52 grams, followed by the first sample at 0.6 grams and the second sample at 0.13 grams. FT-IR can detect microplastics such as polystyrene (PS) and polyvinyl chloride (PVC).